Analisis Sifat Fisik dan Kimia Tanah pada Lahan Aplikasi Limbah Cair Pabrik Kelapa Sawit (LCPKS) dan Tandan Kosong Kelapa Sawit (TKKS) di Perkebunan Kelapa Sawit Kalimantan Barat - Ahmad Khairul Rifki Sitorus; Dian Pratama Putra; Neny Andayani (Program Studi Agroteknologi INSTIPER, 2026)
Palm oil mills generate palm oil mill effluent (POME, locally LCPKS) and empty fruit bunches (EFB, locally tandan kosong kelapa sawit or TKKS), two by-products that estates return to the field as organic amendments. Field comparisons of both materials on the same estate remain scarce in West Kalimantan. This study measured soil physical and chemical properties together with fresh fruit bunch (FFB) production on blocks receiving POME, EFB, or no organic amendment at Seriang Estate, West Kalimantan. The design was observational. The estate had assigned the treatments before sampling began, so treatment allocation was not randomised and no baseline soil data existed. We sampled nine blocks, three per treatment, at 0–30 cm and 30–60 cm, giving 18 samples; each treatment mean therefore rests on six observations drawn from three blocks. Laboratory analyses ran at Institut Pertanian Stiper Yogyakarta and Jungle Point Laboratory between 30 January and 26 February 2025. Production and fertiliser records covered 2021 to 2024. Soil data were analysed by two-way ANOVA with treatment and depth as factors and block as the replicate unit, followed by Duncan Multiple Range Test at the 5% level. Neither POME nor EFB changed any measured soil property. Cation exchange capacity showed the widest gap between means, averaging 90.87 cmol(+)/kg under EFB against 115.22 in the control and 113.42 under POME, but the two-way model did not resolve that gap as significant (p = 0.111). FFB yields did not differ among treatments from 2021 to 2023. Block area, palm stand and fertiliser realisation differed systematically among treatments, so the lower 2024 yield on EFB blocks cannot be attributed to the amendment. Both materials recycle mill nutrients back to the field and supplement mineral fertiliser without replacing it.